PERANCANGAN INTERIOR COWORKING SPACE YANG RAMAH PENYANDANG DISABILITAS - Riza Rohnia Aindi; Sherly de Yong (Intra, 2019)
Nowadays with limited jobs, not onlyfor normal people but also for disabled people that have difficulty to find employment. One of the solutions to this problem is to become an entrepreneur. But another obstacle is expensive rate of office rent. Nowadays, there is a new culture of work called coworking space. The coworking spaces are expected to accommodate number of entrepreneurs who need a place to run their business. In this design project the writer used analytical methods which became the foundation of design thinking. Kembel’s Design Thinking (2009) was chosen to be developed again into design thinking that matched the design. This design is expected not only to be used by normal people who work in this co-working space, but also disabled people.